The Influence Of Tax Incentives, Tax Justice, Profitability, And Ethical Leadership On Tax Compliance - Eriska Widyastuti; Ruklie Abadi; Ika Purwanti (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
This research investigates the interplay between tax compliance and various factors including tax incentives, tax justice, profitability, and ethical leadership. The study aims to discern the nuanced relationships among these variables in the context of compliance behavior. Employing a qualitative research design, semi-structured interviews are conducted with key stakeholders from diverse organizational settings. Sampling techniques involve purposive sampling to ensure representation across sectors and organizational sizes. Data analysis utilizes thematic analysis techniques to identify patterns and themes emerging from the interviews. Preliminary findings suggest complex interactions between tax incentives, perceptions of justice, financial performance, and leadership ethics, shedding light on the multifaceted nature of tax compliance determinants. This research contributes to a deeper understanding of factors influencing tax compliance behaviors and informs policy and organizational strategies aimed at enhancing tax compliance.